EVALUATION ON THE ASSISTANCE OFFERED TO VENOUS ULCERS PATIENTS ATTENDED IN ONOFRE LOPES UNIVERSITY HOSPITAL, IN NATAL / RN: CONSIDERATION OF SOME ASPECTS (Fiep Bulletin - online, 2014)
Descriptive research that objectives evaluate the assistance to individuals with venous ulcers (VU) attended in Onofre Lopes University Hospital (HUOL), in the city of Natal / RN. The target population was composed of 40 VU patients, attended by angiologists and in Surgical Clinic ambulatory of this hospital. The study received assent of the Ethics Committee of Rio Grande do Norte Federal University (Protocol n.169/06). The data-collection was performed in surgical clinic ambulatory of HUOL, through structured interview, non-participant observation in the curative changes and VU patients' records review. In this study, we evaluated that the assistance offered to VUs patients is inappropriate in aspects relating to access of users, number of consultations with angiologists per year, clinical findings documentation and use of compression therapy; And appropriate in relation to the training of professionals and the implementation of specific orientations. With these datas, it may be proposed the establishment of a protocol, together with the service reorganization and replanning, which enables to VUs patients and their families a better quality of assistance.
Keywords: Venous Ulcers; University Hospital; Evaluation